Modern state and prospects of development of the industry of agricultural machinery - Sikorska, Małgorzata; Pererva, P. G. (Харківський національний університет будівництва та архітектури, 2017)
Agricultural engineering must be tailored to the interests and needs of the farmers in full accordance with the plans of agricultural development. In General, the removal of the machine-building complex of the crisis requires the development of a national programmed of development of agricultural mechanical engineering which involves the production of technological complexes of machines and equipment for agriculture, food and processing industry, bringing production of new types of final products and parts to meet the domestic needs by 70%.
Keywords: development; technology transfer; industry; industrial enterprises